If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -13 + -3y + 9 = 0 Reorder the terms: -13 + 9 + 6y + -3y = 0 Combine like terms: -13 + 9 = -4 -4 + 6y + -3y = 0 Combine like terms: 6y + -3y = 3y -4 + 3y = 0 Solving -4 + 3y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 3y = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 3y = 0 + 4 3y = 0 + 4 Combine like terms: 0 + 4 = 4 3y = 4 Divide each side by '3'. y = 1.333333333 Simplifying y = 1.333333333
| 8x-111=-2x+149 | | 3x+5+25+x-10=180 | | -4c+2c+(-5)c=-1 | | G/48=11/12 | | 5x-5=25x-7 | | 6sin^2x+11sinx+5=0 | | 0.5(8c-12)-6=5x-14 | | 484=4+2a*72 | | 2.1x+3.2=-9.4 | | By-3by= | | (3.6+m)7=83.3 | | 6sin^2x-11sinx+5=0 | | 15(t+6m)+9t=6 | | e^2x+1=34 | | 4/3pi10^3 | | (6.3+m)7=83.3 | | 4x+6x-18=72-8x | | 11+a^3=17 | | -2m=4 | | 3z+5=2(z-8) | | 6(2+3x)=192 | | 3t=5-7t-2 | | 12y^2+20y=0 | | -6+6a=108 | | 61=9x+7 | | -19+2x=6+3x | | 38=-2x-2 | | -180*1= | | 2(4+7x)=50 | | 42-4c=2c | | lne^12x=0 | | 3/4m=0 |